Rebels against the Confederacy : North Carolina's unionists - Myers, Barton A., 1980-; Cambridge eBooks (Cambridge : Cambridge University Press, 2014)
In this groundbreaking study, Barton A. Myers analyzes the secret world of hundreds of white and black Southern Unionists as they struggled for survival in a new Confederate world, resisted the imposition of Confederate military and civil authority, began a diffuse underground movement to destroy the Confederacy, joined the United States Army as soldiers, and waged a series of violent guerrilla battles at the local level against other Southerners. Myers also details the work of Confederates as they struggled to build a new nation at the local level and maintain control over manpower, labor, agricultural, and financial resources, which Southern Unionists possessed. The story is not solely one of triumph over adversity but also one of persecution and, ultimately, erasure of these dissidents by the postwar South's Lost Cause mythologizers.
Secession: "it was perfect madness" -- Confederate control: "such a monarchical or tyrannical government" -- Resistance: "I never wanted any other flag to wave over my head" -- Irregular wars: "a state of insurrection against the laws" -- Unionists under reconstruction (and in repose): "I don't feel safe now" -- Epilogue: "all classes in the south united as by magic."
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Unionists (United States Civil War) -- North Carolina; North Carolina -- History -- Civil War, 1861-1865.; Electronic books